Prenatal course of metaphyseal anadysplasia associated with homozygous mutation in MMP9 identified by exome sequencing. Issue 6 (3rd August 2017) - Sharony, R.; Borochowitz, Z.; Cohen, L.; Shtorch‐Asor, A.; Rosenfeld, R.; Modai, S.; Reinstein, E.
Abstract : Metaphyseal anadysplasia (MANDP) is a rare autosomal recessive form of skeletal dysplasia characterized by normal length at birth and transitory bowing of the legs. Although several families with MANDP have been reported, homozygous mutations in the matrix metalloproteinase type 9 ( MMP9 ) gene have been described in only one consanguineous family, and thus the pre and postnatal phenotypic spectrum is still obscure. A clinically similar but more severe type is caused by autosomal‐dominant inheritance and is caused by mutations in matrix metalloproteinase type 13 gene ( MMP13 ). Here, we report the prenatal and early postnatal course of two affected sib fetuses with early sonographic evidence of long bone shortening and postnatally no metaphyseal changes. Whole‐exome sequencing revealed homozygous mutation in MMP9 in both fetuses suggesting a diagnosis of MANDP. We propose that MANDP should be considered in pregnancies with early prenatal shortening of the long bones without associated finding of lethal skeletal dysplasias. In addition, the finding of homozygous mutation in non‐consanguineous parents of Jewish‐Caucasus ancestry may suggest unawareness of such relation or the occurrence of a founder mutation in this gene. Abstract : A, Lateral spine in the neonatal period showing coronal clefts. B, Lateral spine at 5 months showing hyperlordosis resolving coronal clefts and mid lower lumber platyspondyly. C, Lower limbs at the neonatal period showing proportionate shortened limbs with mild bowing of tibiae and fibulae with no metaphyseal changes. D, Anteroposterior of lower limbs at age of 1 year showing somewhat short limbs with no other skeletal changes.